Social Composition, Social Conflict, and Economic Development - Holger Strulik (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2006)
This article shows within a simple growth model how the make up of society affects economic performance when property rights are unenforceable. It investigates behavior of non-cooperative social groups that consume, produce, and appropriate resources either peacefully or through contest. For the case of symmetric groups it is shown that economic growth is generated only in peaceful societies. For the case of asymmetric groups rebel-equilibria are investigated in which a large majority behaves peacefully although challenged by an aggressive minority. In each case it is shown how the possibility of conflict and its intensity and the rate of economic growth depend on social fractionalizaton, general productivity of the economy, and the ease at which resources are appropriated. A final part extends the analysis towards behavior of non-benevolent social elites.
Keywords: C73; D74; O11; 330; Social Conflict; Social Fractionalization; Property Rights; Stagnation; Growth